Strategies Implemented by Top NCAA Olympic Coaches to Enhance Support Surrounding Their Programs - Lee Roberts; Coyte G. Cooper; Erianne A. Weight (Journal of Applied Sports Management, 2013)
A shift in institutional priorities related to profit maximization in “big time” sport programs (men’s basketball and football) has led to the elimination of many men’s Olympic sport programs (Ridpath, Yiamouyiannis, Lawrence, & Galles, 2009). As previous literature has demonstrated, coaches can work toward minimizing elimination decisions by raising money that will limit the financial burden of their program on the athletic department (Weight, 2010). Thus, the purpose of the study was to explore fund-raising practices of top NCAA Division I wrestling coaches (N = 10) to determine strategies that programs can implement to encourage sustainability initiatives. Following the identification of top coaches, respondents were interviewed to determine factors for giving and the best practices being implemented in the field. The interviews were coded and analyzed for common themes. These themes and their subcategories are discussed to provide a foundation for coaches to implement fund-raising initiatives of their own.
Keywords: Fund-raising; program sustainability; relationship building; NCAA wrestling